O USO DO BENZOTRIAZOL NA FOSFATIZAÇÃO DO AÇO CARBONO 1008 COM FOSFATO DE FERRO II - Spagnol, Cristiane (2009)
The phosphating is a chemical process that allows the collection of layers of insoluble metal phosphates, used as pre-treatment system for the painting of ferrous and non ferrous surfaces. The addition of organic substances after the bath of phosphating increases the corrosion resistance of metal substrates. This added protection prevents the appearance of spots in the final product caused by corrosion of the metal part before painting. In this work is the efficiency of inhibitory benzotriazole, the concentration of 10ˉ³ mol Lˉ¹ for carbon steel in 1008 phosphating with iron phosphate, on the means of H2SO4 0.1 mol Lˉ¹, NaOH 0.1 mol Lˉ¹ NaCl and 0.5 mol Lˉ¹. Were employed as techniques: gravimetric analysis, optical microscopy, measurements of open circuit potential, potentiostatic anodic, electrochemical impedance spectroscopy, scanning electron microscopy, spectroscopy scattering of x-ray, revealing the structure of carbon steel, infrared spectroscopy and salt spray analysis. The revelation of the structure of carbon steel in 1008 showed the typical structure ferritic with pearlitic phases in carbon steels. In the H2SO4/BTAH results in decreased density of current at all potentials studied, EIS showing the value of polarization resistance of 33.2 Ωcm² noting the inhibitory effect of BTAH. In the presence of NaCl there is a decrease of potential pites, suggesting an inhibitory action on the nucleation of pites on the metal surface. In medium of NaOH results show no significant action on the use of carbon steel BTAH in 1008 fosfatizado. The results of scanning electron microscopy show that the film of iron phosphate with BTAH presents a more uniform surface on the metal film of iron phosphate. Test of adhesion of the ink on the surface of the carbon steel/iron phosphate/BTAH, there is a structural feature of the best film of phosphate, allowing a better anchoring of the paint on the metallic substrate.